From Text Summarization to Speech Summarization - McKeown, Kathleen; Hirschberg, Julia; Galley, Michel; Maskey, Sameer (IEEE International Conference on Acoustics, Speech, and Signal Processing (ICASSP), 2005)
In this paper, we present approaches used in text summarization, showing how they can be adapted for speech summarization and where they fall short. Informal style and apparent lack of structure in speech mean that the typical approaches used for text summarization must be extended for use with speech. We illustrate how features derived from speech can help determine summary content within two ongoing summarization projects at Columbia University.